O03 Prevalence of fragility fractures and medication prescription for osteoporosis in patients with polymyalgia rheumatica: results from the PMR Cohort Study. (26th April 2021) - Sokhal, Balamrit Singh; Hider, Samantha L; Paskins, Zoe; Mallen, Christian D; Muller, Sara
Abstract: Background/Aims   Polymyalgia rheumatica (PMR) is one of the commonest indications for long term glucocorticoid (GC) use, leading to an increased risk of osteoporosis and fragility fractures. Clinical guidelines recommend prescribing medication including vitamin D, calcium and anti-resorptives, such as bisphosphonates. The aim of this study was to examine the association of reported falls and prescriptions of medications for osteoporosis with future fragility fractures in a cohort of people with PMR. Methods   652 people with an incident diagnosis of PMR responded to a baseline survey between June 2012 and June 2014. This included data on general health, sociodemographics, history of falls and medication. Data on fractures and prescriptions were collected at 12 and 24 months. Fragility fractures were defined as fractures of the hip, wrist or spine. Logistic regression models were used to assess the association between baseline characteristics and fractures at 12 and 24 months. Analysis was conducted unadjusted and adjusted for age, gender, reported medication use and falls history. Results   112 (17.2%) baseline respondents reported a previous fragility fracture. 60 (83.3%) of the 72 respondents who reported a fragility fracture between baseline and month 12 also reported a fragility fracture at baseline. 49 (79.1%) of the 60 respondents who reported a fragility fracture at between the month 12 and 24 also reported a fragility fracture at baseline. Falls before baseline was the most significant predictor of fragility fracture at 12 (OR 2.35 95% CI 1.35-4.12) and 24 (OR 1.91 95% CI 1.05-3.49) months. Fewer than 50% of respondents were ever prescribed treatment for osteoporosis. Being prescribed treatment for osteoporosis was associated with a reduced incidence of fragility fractures at 24 months (adjusted OR 0.28 95% CI 0.10-0.80), but an increased incidence at 12 months (adjusted OR 2.10 95% CI (1.3-3.48). Calcium and vitamin D prescription, gender and age were not significantly associated with fracture outcome. Conclusion   Despite guidelines, fewer than 50% of patients were prescribed medications for osteoporosis. This data highlights the risks of fractures in PMR patients who have experienced previous falls. Over a period of two years, medication for osteoporosis was significantly protective, hence more needs to be done to encourage adherence to guidelines. Further studies need to address reasons for non-adherence to guidelines and the effects of long-term treatment. Disclosure   B. Sokhal: None. S.L. Hider: None. Z. Paskins: None. C.D. Mallen: None. S. Muller: None.